Performances Appraisal of Real Estate Investment Trust in Borsa Istanbul - KAKILLI ACARAVCI, Songul; ACARAVCI, Ali; KARAOMER, Yunus (International Journal of Economics and Financial Issues, 2018)
The Real Estate Investment Trusts (REITs) have an important role in the development of the real estate sector. For investors, the REITs are financial institution that offer service such as professional portfolio management, risk reduced through diversification, and utilization of scale economies. The REITs offer new opportunities for investors by making liquidity high securities the real estate properties in their portfolios. In this paper, the performances of firms traded as the REITs in Borsa Istanbul (BIST) during July 2005 - June 2016 are investigated by employing four different regression models (the Capital Asset Pricing Model - CAPM, Fama-French Three Factor Model - FF[3]F, Fama-French Four Factor Model - FF[4]F, and Fama-French Five Factor Model - FF[5]F). In this manner, regression model is estimated in which returns of the REITs are used as dependent variable; whereas market premium, size premium, value premium, profitability premium, and investment premium are used as independent variables. The Jensen Alpha which is a risk-adjusted performance measure is estimated as fixed term (alpha) between related returns and factors in regression equation. Positive alpha value refers to the risk-adjusted high performance, while negative alpha value refers the risk-adjusted low performance. It is also tested whether the alpha value is different from zero in performance appraisal. Empirical findings suggest that the alpha coefficient is not statistically significant in four different regression models. This result indicate that the REITs do not seem to over perform than market premium, size premium, value premium, profitability premium, and investment premium during the analysis period. Thus, analysts or investors will be able to estimate expected returns by considering these premiums. Keywords: Real Estate Investment Trust, Jensen Alpha, CAPM, Fama-French Factor Models. JEL Classifications: C19, D53, G14 DOI: https://doi.org/10.32479/ijefi.7326